Pendidikan Islam Dan Perubahan Sosial - Salma Bialfi Karimah; Nur Khasanah (Yayasan Al-Afif, 2025)
Islamic education plays an important role in building the social structure of society through the internalization of values, character development, and the strengthening of religious culture. This study aims to examine the relationship between Islamic education and social change in Indonesia, particularly through the contributions of educational institutions such as pesantren and madrasah. The method used in this study is qualitative, with a literature study approach. The results of this study indicate that Islamic education serves as an important agent of social change in strengthening the social, economic, and cultural resilience of society. Pesantren and madrasah are not only places for imparting religious knowledge, but also centers for developing community capacity to adapt to changing times. Islamic values, such as discipline, responsibility, cooperation, and principles of Islamic economics, serve as the foundation for strengthening solidarity.